Multicultural Character Education in Islamic Vocational Schools: A Qualitative Study - Maharani Fadhiyah Haifani; Rochmah Wijayanti; Sabar Narimo; Muh. Musyiam (Institut Agama Islam Negeri Palangka Raya, 2026)
Multicultural value-based character education is increasingly important in vocational schools where students are expected to develop not only technical competence but also social responsibility, tolerance, cooperation, and respect for diversity. This study aims to analyze the implementation of multicultural value-based character education at SMK Muhammadiyah 1 Baturetno, an Islamic vocational school in Central Java, Indonesia. A qualitative approach with a descriptive-analytical design was employed. Data were collected through in-depth interviews with the principal, teachers, and students, non-participant observation of classroom and school activities, and document analysis. The data were analyzed using data condensation, data display, and conclusion drawing, supported by source and technique triangulation. The findings show that character education is integrated into classroom learning, religious habituation, extracurricular activities, school discipline, teacher role modelling, and daily social interaction. Character values such as religiosity, discipline, responsibility, cooperation, and social care are reinforced alongside multicultural values, including tolerance, respect for diversity, equality, and non-discrimination. The study also reveals that teachers play a central role in modelling inclusive behaviour and using dialogue to guide students’ character development. However, implementation remains challenged by uneven teacher understanding and inconsistent value integration across school practices. This study contributes to the literature by showing how an Islamic vocational school can connect religiously grounded character formation with multicultural and inclusive social interaction.